Median Group® in a Psychiatric Outpatient Service and in a Psychiatric Diagnosis and Treatment Service (SPDC). (June 2013) - Schoellberger, Roberto; Pozzi, Laura
Outlined is a brief description of two pieces of research into the Median Group experience in an open psychiatric outpatient service and in a closed ward. The first is about the self-definition and well being of 30 patients in three Median Groups, mostly under drug prescription, and 31 patients only under drug prescription. On nine sub scales (five levels each) of SCL (Symptom Check List)-90-R, only the field of somatization shows small differences between the experimental and the control group, whereas in all the others the differences are statistically significant, which means a better quality of life. The other research has been undertaken by Laura Pozzi, who introduced the Median Group to a closed psychiatric ward of a general hospital. It shows a high level of acceptance within the group, and on the group ward level, a sudden decrease of aggressive episodes has been registered.